1998
DOI: 10.1038/sj.leu.2401012
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic malignancies with t(4;11)(q21;q23) – a cytogenetic, morphologic, immunophenotypic and clinical study of 183 cases

Abstract: A total of 183 hematologic malignancies with t(4;11)(q21;q23), including five variant translocations, were collected by the Workshop. Clinical, morphologic and immunophenotypic features were compiled, and karyotypes with variant t(4;11) or secondary chromosomal aberrations were reviewed. All cases were acute leukemias (AL): 173 acute lymphoblastic leukemias (ALL), six acute myeloid leukemias (AML), three unclassifiable AL, and one biphenotypic AL. Ten patients had treatment-associated AL. Females were overrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 30 publications
(60 reference statements)
2
82
0
2
Order By: Relevance
“…This parallels findings from the European Union Concerted Action Workshop on 11q23: among ALL patients with t(4;11)(q21;q23) 15% (26/173) were classified as pre-B ALL and del(11)(q23) has also been demonstrated in pre-B-ALL. 22,23 Thus, the close association between NG2 positivity and the presence of MLL rearrangement in these nine patients with pre-B-ALL strongly suggest that these patients are at an increased risk for treatment failure. The fact that none of our patients with mature B-ALL and T-ALL showed NG2 expression corresponds to previous findings.…”
Section: Discussionmentioning
confidence: 86%
“…This parallels findings from the European Union Concerted Action Workshop on 11q23: among ALL patients with t(4;11)(q21;q23) 15% (26/173) were classified as pre-B ALL and del(11)(q23) has also been demonstrated in pre-B-ALL. 22,23 Thus, the close association between NG2 positivity and the presence of MLL rearrangement in these nine patients with pre-B-ALL strongly suggest that these patients are at an increased risk for treatment failure. The fact that none of our patients with mature B-ALL and T-ALL showed NG2 expression corresponds to previous findings.…”
Section: Discussionmentioning
confidence: 86%
“…4,70 The t(4;11)(q21;q23) and t(11;19)(q23;p13.3) are the most common translocations in ALL, whereas t(6;11)(q27;q23), t(9;11)(p21-p22;q23), t(10;11)(p12;q23), and t(11;19)(q23;p13.1) are most frequent in AML. [71][72][73][74][75][76] The MLL gene is the human homologue of the Drosophila trithorax gene. 77 The MLL protein contains a transcription repression domain, a transcription activation domain, and two types of DNA-binding domains (minor groove DNA-binding 'AT-hook' motifs and major groove DNA-binding zinc-fingers).…”
Section: Translocations Involving the Mll Gene (11q23)mentioning
confidence: 99%
“…Among B-lineage ALL cases with the t(4;11)(q21;q23) or t(11;19)(q23;p13.3), infants less than 12 months of age have a poor outcome, whereas those 1 to 9 years old have a relatively favorable prognosis. [24][25][26] A limited study suggested that prednisone response can further discriminate two prognostic groups among infants with the t(4;11). 27 However, neither bone marrow nor peripheral blood response after 8 days of remission induction therapy with prednisone, vincristine, daunorubicin and asparaginase, was predictive of event-free survival among 51 infants treated on a recent Medical Research Council (MRC) infant ALL protocol.…”
Section: Leukemia With 11q23 Rearrangementmentioning
confidence: 99%